Fluorescent superparamagnetic iron oxide core-shell nanoprobes for multimodal cellular imaging - Smitha, Sasidharan; Haseena, Vadakkenchery S.; Narayanan, Tharangattu N.; Mary, Antony P. Reena; Ajayan, Pulickel M.; Puthumana, Jayesh; Aziz, Anas A.; Aburto, Rebeca R.; Mani, Sendurai A.; Joy, Pattayil Alias; Anantharaman, Maliemadom R. (Materials Express, 2012)
Multimodal imaging agents that combine magnetic and fluorescent imaging capabilities are desirable for the high spatial and temporal resolution. In the present work, we report the synthesis of multifunctional fluorescent ferrofluids using iron oxide as the magnetic core and rhodamine B as fluorochrome shell. The core-shell structure was designed in such a way that fluorescence quenching due to the inner magnetic core was minimized by an intermediate layer of silica. The intermediate passive layer of silica was realized by a novel method which involves the esterification reaction between the epoxy group of prehydrolysed 3-Glyidoxypropyltrimethoxysilane and the surfactant over iron oxide. The as-synthesized ferrofluids have a high saturation magnetization in the range of 62-65 emu/g and were found to emit light of wavelength 640 nm (lambda(excitation) = 446 nm). Time resolved life time decay analysis showed a bi-exponential decay pattern with an increase in the decay life time in the presence of intermediate silica layer. Cytotoxicity studies confirmed the cell viability of these materials. The in vitro MRI imaging illustrated a high contrast when these multimodal nano probes were employed and the R2 relaxivity of these sample was found to be 334 mM(-1)s(-1) which reveals its high potential as a T2 contrast enhancing agent.
Keywords: GPTMS; MRI Imaging; Multimodal Imaging; SPION; T2 Contrast Agent

Contact potential induced enhancement of magnetization in polyaniline coated nanomagnetic iron oxides by plasma polymerization - Sethulakshmi, N.; Sooraj, V.; Sajeev, U. S.; Nair, Swapna S.; Narayanan, T. N.; Joy, Lija K.; Joy, Pattayil Alias; Ajayan, Pulickel M.; Anantharaman, Maliemadom R. (Applied Physics Letters, 2013)
The present work derives motivation from the so called surface/interfacial magnetism in core shell structures and commercial samples of Fe3O4 and gamma Fe2O3 with sizes ranging from 20 to 30 nm were coated with polyaniline using plasma polymerization and studied. The High Resolution Transmission Electron Microscopy images indicate a core shell structure after polyaniline coating and exhibited an increase in saturation magnetization by 2 emu/g. For confirmation, plasma polymerization was performed on maghemite nanoparticles which also exhibited an increase in saturation magnetization. This enhanced magnetization is rather surprising and the reason is found to be an interfacial phenomenon resulting from a contact potential. (C) 2013 AIP Publishing LLC.

Synthesis of N, F and S co-doped graphene quantum dots - Kundu, Sumana; Yadav, Ram Manohar; Narayanan, T. N.; Shelke, Manjusha V.; Vajtai, Robert; Ajayan, Pulickel M.; Pillai, Vijayamohanan K. (Nanoscale, 2015)
Graphene quantum dots (GQDs) are a promising category of materials with remarkable size dependent properties like tunable bandgap and photoluminescence along with the possibility of effective chemical functionalization. Doping of GQDs with heteroatoms is an interesting way of regulating their properties. Herein, we report a facile and scalable one-step synthesis of luminescent GQDs, substitutionally co-doped with N, F and S, of similar to 2 nm average size by a microwave treatment of multi-walled carbon nanotubes in a customized ionic liquid medium. The use of an ionic liquid coupled with the use of a microwave technique enables not only an ultrafast process for the synthesis of co-doped GQDs, but also provides excellent photoluminescence quantum yield (70%), perhaps due to the interaction of defect clusters and dopants.

Facile green synthesis of BCN nanosheets as high-performance electrode material for electrochemical energy storage - Karbhal, Indrapal; Devarapalli, Rami Reddy; Debgupta, Joyashish; Pillai, Vijayamohanan K.; Ajayan, Pulickel M.; Shelke, Manjusha V. (Chemistry-A European Journal, 2016)
Two-dimensional hexagonal boron carbon nitride (BCN) nanosheets (NSs) were synthesized by new approach in which a mixture of glucose and an adduct of boric acid (H3BO3) and urea (NH2CONH2) is heated at 900 degrees C. The method is green, scalable and gives a high yield of BCN NSs with average size of about 1 mm and thickness of about 13 nm. Structural characterization of the as-synthesized material was carried out by several techniques, and its energy-storage properties were evaluated electrochemically. The material showed excellent capacitive behaviour with a specific capacitance as high as 244 F g(-1) at a current density of 1 A g(-1). The material retains up to 96% of its initial capacity after 3000 cycles at a current density of 5 A g(-1).
Keywords: boron; Doping; Electrochemistry; Nanoparticles; nitrides

Facile synthesis of 3D anode assembly with Si nanoparticles sealed in highly pure few layer graphene deposited on porous current collector for long life Li‐Ion battery - Shelke, Manjusha V.; Gullapalli, Hemtej; Kalaga, Kaushik; Rodrigues, Marco; Devarapalli, Rami Reddy; Vajtai, Robert; Ajayan, Pulickel M. (Advanced Materials Interfaces, 2017)
With its exceptional theoretical charge capacity, silicon holds great promise as an anode material for realization of high energy density Li-ion batteries. However, extensive volume expansion and poor cycle stability of silicon compromise its actual use. In an effort to tame volume expansion and structural disintegration during cycling, an innovative 3D electrode assembly is fabricated involving continuous layer of graphene coated on porous current collector and Si nanoparticles sealed in as an active material. Graphene deposition and pore formation in metal current collector is achieved in a unique single step synthesis. All the active components like current collector, reacting material, and conducting material are manipulated in a way to produce synergistic architecture in a chemical vapor deposition process. Highly pure graphene deposited in this process enables efficient electron transfer from allover of the surface of silicon nanoparticles and prevents continuous solid electrolyte interphase layer formation. This binder free anode assembly shows extremely stable lithium storage performance for over 1000 cycles with 88% of initial capacity retention and 100% Coulombic efficiency.

Atomic Layer Deposition Grown Titania Phases (TiO2, TiO, Ti2O) and its Influence on Water Splitting Electrocatalysis - Swaminathan, Jayashree; Palani, Parthiban; Salpekar, Devashish; Hernandez, Francisco Carlos Robles; Ashokkumar, Meiyazhagan; Ajayan, Pulickel M. (Advanced Sustainable Systems, 2025)
The systematic engineering of atoms and the precise tuning of their arrangement can unlock a range of hidden yet remarkable properties of materials. In this study, different phases of titanium oxide, including TiO2, TiO, and Ti2O, are developed using the Atomic Layer Deposition (ALD) technique. Notably, a novel TiO(2 )electride with a pbcn space group is identified, and variations in stoichiometries, such as Ti1.80O, Ti2.05O, and Ti2.30O, are observed through Rietveld analysis of the corresponding X-ray Diffraction (XRD) data. High-resolution transmission electron microscopy (HRTEM) imaging further revealed line defects such as stacking faults and edge dislocations in Ti2O. The interplay of stoichiometric defects in Ti2O electrides leads to tunable electrocatalytic behavior, enabling transitions from oxygen evolution to hydrogen evolution reactions. Importantly, using Density functional theory (DFT), Paterson analysis, and Fourier electron density mapping, the exceptional metallic properties of Ti2O are rationalized as arising from its unique spatial electron density distribution. Overall, this work underscores the significance of atomic-level structure engineering and opens the door to a new class of titanium oxide catalysts for electrochemical water splitting.
Keywords: atomic layer deposition; defect engineering; defect-rich titania; Electrocatalytic water splitting; Ti2O electrides